KAJIAN KEBIJAKAN RELOKASI TERAS MALIOBORO DALAM RANGKA OPTIMALISASI MINAT BELANJA WISATAWAN DAN PENINGKATAN PAD PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Wardhani, Shita Lusi Wardhani; Kusuma, Manggar Wulan (Jurnal Ekonomi Dan Bisnis, 2023)
Optimizing the role of Teras Malioboro in increasing PAD, the Provincial Government plans to concentrate the location of street vendors into one location in the Teras Malioboro I area. In 2023, the DIY Provincial Government plans to immediately build a new tourist spot in the Malioboro area, namely the Jogja Planning Gallery. The location chosen to build the building is Teras Malioboro 2 so the DIY Provincial Government plans to move Teras Malioboro 2 to the Teras Malioboro 1 area. This policy was implemented so that street vendors can get more representative locations because the current locations are felt to be uneven. With this concentration, it is hoped that tourists will find convenience and comfort in shopping. This research measures the influence of store atmosphere and location on tourists' buying interest and tourists' regional origin as moderating variables. SEM analysis using SmartPLS software was used in this research. The research results show that the store atmosphere and location of the Malioboro terrace are able to influence tourists' buying interest. The results of this research prove that this policy is appropriate to implement. The more strategic the location of Malioboro Terrace, the more tourists will be interested in shopping, because they won't have to have difficulty reaching that location. This research also proves that the region where tourists come from can strengthen the influence of store atmosphere and location on tourists' buying interest.